Russian-Chinese Relations: From the Decision of Interstate Problems to the Strategic Partnership - BUYAROV, Dmitry Vladimiriovich; KIREEV, Alexey Aleksandrovich; DRUZYAKA, Andrey Victorovich (Journal of Advanced Research in Law and Economics; Vol 6 No 4 (2015): JARLE Volume VI, Issue 4(14), Winter 2015, 2017)
The article explores the history of bilateral relations between Russia and China. It is noted that the state of these relations was going upward, gradually expanding. Interstate relations are considered through a series of agreements concluded by Russia and China for nearly four centuries. These documents fixed the state of mutual understanding between the two countries. For four centuries, Russia and China have gone the way from confrontation and arrangements regarding inter-state problems to the state of strategic partnership. Countries were able to overcome mutual hostility and moved to the process of solving problems. The main problem for a long time was the problem of the border demarcation. Its decision marked the relations between Russia and China to a new level, free from confrontation. The top of the process of the rapprochement between the two states at the present stage is the ‘Treaty of Good-Neighborliness, Friendship and Cooperation’ signed between the Russian Federation and the People's Republic of China in 2001. This document is analyzed in the context of the continuity of bilateral relations and the current international situation. The strategic partnership is reflected in the joint participation of Russia and China in solving regional and global problems, development of political and socio-economic relations.